How do you solve this equation? -aln(a-x)=ln(t-b)

-aln(a-x)=ln(t-b)
Solve for x.

1 Answer
Apr 17, 2016

x = a - root(a)(1/(t-b))" " if a != 0

x < 0" " if a = 0

Explanation:

Your equation looks like this

-a * ln(a-x) = ln(t-b)

You're dealing with natural logs, so right from the start you know that you must have

a -x > 0" " and " " t -b > 0" " " "color(orange)("(*)")

since you can't take the natural log of zero or a negative number while working in RR.

Next, we need to split into cases a = 0 and a != 0

Case bb(a = 0)

In this case we have

0 = ln(t-b)

So

t - b = 1

Adding b to both sides we find

t = b + 1

The value of x is unconstrained except that we require

a - x > 0

Hence

x < 0

Case bb(a != 0)

With a != 0 we can first divide both sides of the equation by -a to get

ln(a - x) = ln(t-b) * -1/a

Then taking exponents of both sides

e^(ln(a-x)) = e^(ln(t-b)*-1/a)

Note that if r > 0 then

e^ln(r) = r

Also if A > 0 and B, C in RR, then

A^(BC) = (A^B)^C

So our equation simplifies to

a-x = (t-b)^(-1/a)

Hence

x = a - (t-b)^(-1/a) = a - root(a)(1/(t-b))

Note that since t-b > 0 we also have

1/(t-b) > 0

and the principal ath root represented by

root(a)(1/(t-b))

is a well-defined positive Real number.